Laser-induced plasma-assisted ablation (LIPAA) of glass: Effects of the laser fluence on plasma parameters and crater morphology. (December 2019) - Rahman, T.U.; Rehman, Z.U.; Ullah, S.; Qayyum, H.; Shafique, B.; Ali, R.; Liaqat, U.; Dogar, A.H.; Qayyum, A.
Highlights: Morphology of crater changes with fluence and target-to-substrate distance. Variation in crater size and plasma parameters with laser fluence were identical. Size of crater depends on radial dimension, temperature and density of the plasma. Size of crater get saturated at higher fluence levels. Laser absorption in the plasma is responsible for the saturation of crater size. Abstract: This paper reports the fabrication of micro-craters on the soda lime glass substrate by laser-induced plasma-assisted ablation (LIPAA) using a Q-switched Nd-YAG laser (wavelength = 1064 nm, pulsed width = 6 ns). The objectives were to investigate the effects of laser fluence and target-to-substrate distance on the morphology of micro-craters, and to relate the observed effects with the plasma parameters. The incident laser fluence at the sacrificial aluminium target was in the range of 27–870 J/cm 2 and target-to-substrate distance was in the range of 0 to 600 μm. The micro-craters were analyzed with the help of optical microscope and profilometer. And the plasma parameters were measured using the optical emission spectroscopy. Our results showed that the diameter and depth of micro-craters increases with the laser fluence and seems to reach saturation at higher fluence levels. However, the diameter and depth of the micro-craters were found to decrease linearly with the increase of target-to-substrate distance. The electron temperature and density of the aluminium plasma estimated using Boltzmann plot and Stark broadening methods were in the range of 6320–11450 K and 7.78 × 10 16 –2.0 × 10 17  cm −3, respectively. The variation of plasma parameters as a function of the laser fluence was quite identical to the change in the size of micro-craters. The experimental results are discussed on the basis of LIPAA models and plasma shielding of the laser radiation.